3D Dynamic Programming Approach to Functional Equations with Applications. (21st September 2020) - Asif, Awais; Khan, Sami Ullah; Abdeljawad, Thabet; Arshad, Muahammad; Ali, Amjad
Abstract : This article demonstrates the graphical existence of a single fixed point while imposing the contractive condition of Chatterjea type F -contraction on F -metric space (briefly as F -MS). We present two examples that verify the validity of the results given in the paper. The paper further explains the subsistence of the fixed point even if the contractive condition is valid only for a closed ball inside the space rather than imposing it on the whole F -MS. Moreover, the application of the mentioned results in finding a single solution of functional equations is described that is widely used in computer programming and optimization.